Effects of acupuncture on the pregnancy outcomes of frozen-thawed embryo transfer: A systematic review and meta-analysis - Zhu, Can; Xia, Wanting; Huang, Jinzhu; Zhang, Xuan; Li, Fangyuan; Yu, Xiaorun; Ma, Jiamin; Zeng, Qian (Frontiers in Public Health, 2022)
Background: Acupuncture is increasingly used as an adjuvant therapy for infertile women undergoing frozen-thawed embryo transfer (FET); however, the effects and safety of it are highly controversial. The aim of this study was to evaluate the pooled effects of adjuvant acupuncture on FET pregnancy outcomes. Methods: We considered only randomized controlled trials (RCTs) that compared acupuncture with sham acupuncture or no adjuvant treatment during FET and the primary outcome was clinical pregnancy rate. Two authors separately selected studies, extracted data and performed risk of bias assessment. Pooled data was expressed as risk ratio (RR) or mean difference (MD), with 95% confidence interval (CI). In addition, we conducted subgroup and sensitivity analyses to investigate sources of heterogeneity, and we also constructed funnel plots to assess the likelihood of publication bias. Finally, Grading of Recommendation, Assessment, Development and Evaluation (GRADE) was applied to evaluate the quality of evidence. Results: 14 RCTs with a total of 1130 participants were included in the study. We found significant effects of acupuncture adjuvant to FET on the outcomes of clinical pregnancy rate (RR = 1.54, 95%CI [1.28, 1.85], I2 = 34%; 14 trials), biochemical pregnancy rate (RR = 1.51, 95%CI [1.21, 1.89]; 5 trials), endometrial thickness (MD = 0.97, 95%CI [0.43, 1.51]; 12 trials), and endometrial pattern (RR = 1.41, 95%CI [1.13, 1.75]; 7 trials). For live birth rate (RR = 1.48, 95%CI [0.90, 2.43], 4 trials), there were no statistical effectiveness. For subgroup analyses, most variables had tolerable heterogeneity (I2 = 0%) except for trials that were sham-controlled, performed acupuncture only after FET or less than 5 times, which appeared to interpret most of the heterogeneity. Additionally, the quality of evidence of all outcomes in this review ranged from low to moderate. Conclusion: Acupuncture could be instrumental in the pregnancy outcomes of FET, and has very few risks of severe adverse events; however, the quality of evidence is unsatisfied. Further researches with rigorous methodological quality should be considered, and the protocols of acupuncture also need more investigations (eg., appropriate control groups, sessions and times).